An Investigation Of A New Hybrid Conjugates Gradient Approach For Unconstrained Optimization Problems - Rahma F. Aziz; Maha S. Younis; Marwan S. Jameel (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This work introduces a novel hybrid conjugate gradient (CG) technique for tackling unconstrained optimisation problems with improved efficiency and effectiveness. The parameter is computed as a convex combination of the standard conjugate gradient techniques using and . Our proposed method has shown that when using the strong Wolfe-line-search(SWC) under specific conditions, it achieves global theoretical convergence. In addition, the new hybrid CG approach has the ability to generate a search direction that moves downward with each iteration. The quantitative findings obtained by applying the recommended technique about 30 functions with varying dimensions clearly illustrate its effectiveness and potential.